POLA ASUH DAN PEMBINAAN SOSIAL REMAJA PADA PONDOK PESANTREN - MUMU MUKHLISIN (ACADEMIA: Jurnal Inovasi Riset Akademik, 2021)
Islamic Boarding School education (Pesantren) began to be in great demand by the community as a place for formal and informal education. The main attraction of pesantren education is the embeded of character and religious knowledge which cannot be obtained in formal education. The application of Islamic character habituation applied to the daily life of students (santri) in Islamic boarding schools cannot be separated from the role of Kyai, Nyai as well as ustadz and ustadzah. The pattern of parenting and social development applied to students aims to change the students characters into virtuous characters in accordance with Islamic concepts. The habituation of Islamic character is carried out through the daily activities of students in Islamic boarding schools. This research with a theoretical approach tries to analyze the concept of parenting and social development of adolescents applied in Islamic boarding schools. The results of this study indicate that Parenting at Darunnajah Islamic Boarding School uses democratic parenting. The role of Kyai and Nyai as role models and mentors is a form of embodiment of religious characters. The application of discipline in the Islamic Boarding School did by using democratic and responsible parenting approach. ABSTRAKPendidikan Pondok Pesantren (Pesantren) mulai banyak diminati oleh masyarakat sebagai wadah pendidikan formal maupun informal. Daya tarik utama pendidikan pesantren adalah tertanamnya budi pekerti dan ilmu agama yang tidak dapat diperoleh dalam pendidikan formal. Penerapan pembiasaan karakter Islami yang diterapkan dalam kehidupan sehari-hari santri (santri) di pondok pesantren tidak lepas dari peran Kyai, Nyai serta ustadz dan ustadzah. Pola asuh dan pengembangan sosial yang diterapkan pada siswa bertujuan untuk mengubah karakter siswa menjadi karakter yang berbudi luhur sesuai dengan konsep Islam. Pembiasaan karakter islami dilakukan melalui aktivitas keseharian santri di pondok pesantren. Penelitian dengan pendekatan teoritis ini mencoba menganalisis konsep pola asuh dan perkembangan sosial remaja yang diterapkan di pondok pesantren. Hasil penelitian ini menunjukkan bahwa Pola asuh di Pondok Pesantren Darunnajah menggunakan pola asuh demokratis. Peran Kyai dan Nyai sebagai suri tauladan dan pembimbing merupakan salah satu bentuk perwujudan karakter religius. Penerapan disiplin di Pondok Pesantren dilakukan dengan menggunakan pendekatan pola asuh yang demokratis dan bertanggung jawab.